SoFA: A matlab‐based educational software for the shallow foundation analysis and design. Issue 2 (1st February 2017) - Nikolaou, Konstantinos; Pitilakis, Dimitris
ABSTRACT: Shallow Foundation Analysis (SoFA) software is a newly‐developed free stand‐alone program based on Matlab for the calculation of bearing capacity and settlements of shallow foundations. SoFA uses several well‐known formulas from the literature and design codes that are preferred in engineering practice and not complicated numerical methods. The main goal is to provide the end‐user (student, academic, or professional civil engineer) with a simple, useful, user‐friendly tool to perform preliminary assessment of foundation analysis. © 2017 Wiley Periodicals, Inc. Comput Appl Eng Educ 25:214–221, 2017; View this article online atwileyonlinelibrary.com/journal/cae ; DOI10.1002/cae.21791